Perspectives of using the didactic game for teaching Romanian language and literature - Alexandru BĂRDUȚ (Association of Social and Educational Innovation, 2018)
This paper presents the possibilities of implementing the game in the teaching-learning process. In this way, the game acquires a new dimension, that of didactic game. The presented theoretical aspects support the use of the game in this process. Didactic games offer advantages to both the teacher and the students. The information transmitted through this method is easily assimilated by students who can develop behaviours, attitudes or beliefs. However, all this can be done under the careful coordination of the teacher, in order to avoid possible deviations leading to failure.